If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(-5xy) = a Remove parenthesis around (-5xy) 3x * -5xy = a Reorder the terms for easier multiplication: 3 * -5x * xy = a Multiply 3 * -5 -15x * xy = a Multiply x * xy -15x2y = a Solving -15x2y = a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-15y'. x2 = -0.06666666667ay-1 Simplifying x2 = -0.06666666667ay-1 Reorder the terms: 0.06666666667ay-1 + x2 = -0.06666666667ay-1 + 0.06666666667ay-1 Combine like terms: -0.06666666667ay-1 + 0.06666666667ay-1 = 0.00000000000 0.06666666667ay-1 + x2 = 0.00000000000 The solution to this equation could not be determined.
| 5x-4(x-7)=4+2x | | 99+m^2=0 | | 7x+8y-9z=6 | | 13x+13=62-4x | | 14x=-7 | | -35=5y | | -20=-5y | | 63=9y | | c^2=7c+18 | | -m^2-12=87 | | 4x+38=7x+20 | | X^2+4x^2+24x+24=4x^2+24x+36 | | 7+5a=8+2a | | 2x-3(x+6)=-4x(x-1) | | 7+7a+5a^2=8+2a+2a^2 | | 3y^2+10y=17y^2 | | -9x+4=2x+24 | | b^2+10b+9=0 | | 3(4x-1)=2(5x+4) | | 5x+7y=6 | | 6x-7=m | | 75-4x=32x+23 | | 3t-4=y | | (x+6)(x-2)=-7 | | V-3d=z | | 3x^2+4xy^2=1 | | 63-3x=6x+23 | | 1-2=-1 | | 14-8x=30-15x | | x*x=10-3X | | 5x-30=4x+2 | | 2x+23=10x-49 |